A stratégiai tervezés szerepe a vállalat életében - tervezési problémák, hiányosságok a Sága Foods Zrt.-nél - Bejczi László (2019)
The subject of my thesis is the role of strategic planning and its relevancy and significance in a company’s operations. The modern economy and fierce competition have forced companies to think through, set, and communicate achievable and measurable expectations. In order to set these expectations, a company must understand internal and external factors influencing success and evaluate how to realistically apply both human and monetary resources through strategic planning. The goal of strategic planning is to formulate and implement the vision that drives the company forward, contributes toward employee development, and increases the company’s competitiveness in the marketplace. I investigated the company’s strategic and operational plans, with special focus given to the BCG matrix as well as the use of the Balanced Scorecard. Based on available information about Saga Foods Zrt combined with interviews I present key tools of strategic planning. The goal of my thesis is to highlight the importance of strategic planning and identify deficiencies and problems with the strategic planning process at Saga Foods Zrt. I prepared my thesis based on systematically evaluating industry resources, performing financial analysis, and reviewing internal company data available to me. I referenced and assessed the thoughts of industry experts, and dounded those out with my own judgement and expertise. I familiarized myself with Saga Foods Zrt. and assessed its stra-tegic plan through reviewing the company’s annual reports, financial analysis, and other internal company data. With my professional review, I address the topics of strategic planning, strategic management, and operational planning. I separately discuss the Balanced Scorecard. In the empirical phase of my thesis I applied theory into practice. After assessing Saga Foods Zrt’s market environment, I formulated the significant factors impacting the imple-mentation of strategic planning. Applying theoretical knowledge and practical experience, I prepared the company’s BCG matrix and the Balance Scorecard system. Furthermore, I have drawn a conclusion and proposed improvements that shall help the company’s competitiveness.